Green Tea Intake and Parkinson's Disease Progression: A Mendelian Randomization Study - Li, Chunyu; Lin, Junyu; Yang, Tianmi; Shang, Huifang (Frontiers in Nutrition, 2022)
Epidemiological studies have suggested green tea intake was associated with a reduced risk of Parkinson’s disease (PD). However, whether green tea intake has an effect on PD progression is unknown. To evaluate the role of green tea intake in PD progression, we conducted a two-sample Mendelian randomization analysis using summary statistics from genome-wide association studies of green tea intake (N = 64,949), age at onset (N = 28,568) and progression (N = 4,093) of PD. One standard deviation increase in genetically determined green tea intake was significantly associated with slower progression to dementia (OR: 0.87, 95% CI: 0.81~0.94, P: 3.48E-04) after the Bonferroni correction. Meanwhile, higher green tea intake was nominally associated with slower progression to depression, and lower risk of dementia, depression, hyposmia and insomnia at baseline. The results were robust under all sensitivity analyses. These results might facilitate novel therapeutic targets to slow down the progression of PD in clinical trials, and have clinical implications for patients with PD.